Synthesis and biological evaluation of new titanium (IV) complexes and their use in anti-cancer treatment - ABID, Mohammed Adnan (2021)
This thesis considers the synthesis, and characterisation of new fulvene ligands and titanium(IV) complexes and evaluation of their potential as anti-cancer agents. It contains the in vitro cell results from different techniques used to investigate their biological mechanisms of action and their activity against human cancer cell lines.